Therapeutic Targeting of GSK3β-Regulated Nrf2 and NFκB Signaling Pathways by Salvianolic Acid A Ameliorates Peritoneal Fibrosis - Zhou, Fan; Yao, Lan; Lu, Xiaoqing; Li, Yubao; Han, Xingmin; Wang, Pei (Frontiers in Medicine, 2022)
Peritoneal fibrosis is a devastating complication in patients undergoing peritoneal dialysis, with no definite therapy yet available. Salvia miltiorrhiza and its major active component Salvianolic acid A (Sal A) have demonstrated a beneficial effect in myriad diseases. However, their effect on peritoneal fibrosis is unknown. In murine models of peritoneal dialysis, daily Sal A treatment substantially improved the peritoneal dialysis fluid (PDF) elicited peritoneal fibrosis, marked by thickening of the submesothelial compact zone, accumulation of extracellular matrix and in-creased expression of vimentin and PAI-1, concomitant with attenuation of GSK3β hyperactivity. This coincided with diminished nitrotyrosine in peritoneal tissues and increased Nrf2 nuclear translocation, entailing a lessened oxidative injury and reinforced Nrf2 antioxidant response. Meanwhile, inflammatory infiltration and maladaptive angiogenesis in peritoneal tissues provoked by PDF injury were also mitigated by Sal A, associated with a suppressed NFκB activation. Mechanistically, ectopic expression of the constitutively active GSK3β blunted the NFκB-suppressing and Nrf2-activating efficacy of Sal A in peritoneal mesothelial cells exposed to hypertonic dextrose, suggesting that GSK3β inhibition mediates the protective effect of Sal A. Collectively, our findings may open the avenue for developing a novel therapy based on Sal A for preventing peritoneal fibrosis in peritoneal dialysis.